The Effectiveness of Bulletin Boards as a Creative Outlet for Students in Developing Talents - Jumiarti, Desri; Rahmi, Fadila; Damrah, Dila Rahmii (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Basic education is a critical stage in the formation of students' character and potential. In an effort to develop children's talents and creativity at elementary school (SD) level, the use of Wall Media (Mading) has become the focus of attention. This article investigates the effectiveness of Mading as a medium that encourages elementary school students' creativity. The research method involves literature study and relevant previous research. The study results show that Mading is effective in providing space for creative expression for students, improving their social skills, and strengthening interest in learning. Apart from that, Mading also functions as an informal educational medium that can enrich students' knowledge outside the formal curriculum.┬á